#TITLE_ALTERNATIVE# - ADI PRAKOSO (NIM 12104096); Pembimbing : Dr. Ir. Edy Sanwani, MT, PULUNG
Underground mine refilling process (backfilling) is one of important factors in cut and fill mining system that is applied at PT Antam Tbk UBPE Pongkor. Before the tailing slurry is filled into stope, it is precipitated in a thickener unit to improve percent solid of underflow (become 55-60% solid) and produce clear overflow water. The underflow is used for backfilling whereas the overflow is used for drilling process in underground mine. To produce a high quality of overflow and quick precipitation process, agglomerating materials, called as coagulant and flocculant, are required to be added into the thickener. The function of coagulant is to neutralize fine particle's charge, so that the effective gap of London-Van Der Waals forces can be increased and small particles could be formed. Flocculant could agglomerate tailing solid particles and therefore a faster sedimentation process can be obtained. In the actual condition, clear overflow could not be produced, so that the mining process could also be obstructed. To find the best and suitable coagulant and flocculant concentrations (dosages) for thickening process, the coagulant and flocculant must be tested by batch sedimentation in laboratory. Variables for sediment test were chosen in relation with operating conditions in the thickener. Basically, the test variables are factors that affect coagulation and flocculation processes such as concentration of coagulant and flocculant, percent solid of tailing, acidity (pH), and coagulant and flocculant dosages. The results of experiment shows that slurry conditions with 21%-solids and pH 8 are the optimum and effective conditions. This slurry require coagulant concentration of 5 kg/125 L (40,000 ppm), coagulant dosage of 82.94 gr/dry ton solid tailing, flocculant concentration of 1.5 kg/m3 (1,500 ppm), flocculant dosage of 16.17 gr/dry ton solid tailing to precipitate. These operating conditions produce sedimentation rate of 5.07 m/hour and clear overflow with total suspended solid of 27 mg/L. Furthermore, from the results of experiment and operational cost optimation it was shown that operational cost could be saved by 8.97%.